2003
DOI: 10.1096/fj.02-0654rev
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of apoptosis: the ubiquitous way

Abstract: Ubiquitin is a ubiquitously expressed 76 amino acid protein that can be covalently attached to target proteins, leading to their ubiquitination. Many ubiquitinated proteins are degraded by the proteasome, a 2000 kDa ATP-dependent proteolytic complex. Numerous studies have demonstrated that the ubiquitination and proteasome system plays an important role in controlling the levels of various cellular proteins and therefore regulates basic cellular processes such as cell cycle progression, signal transduction, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
122
0
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 205 publications
(128 citation statements)
references
References 117 publications
5
122
0
1
Order By: Relevance
“…Despite the presumed role of XIAP in targeting caspases for proteasomal degradation, 9 the loss of XIAP did not result in an accumulation of procaspases, possibly because of autoactivation and autoprocessing. The loss of XIAP was delayed by the broad-spectrum caspase inhibitor, zVADfmk, suggesting that XIAP was not only depleted by antisense expression but also became a substrate for activated caspases, as previously observed during Ad-XIAP antisense gene therapy for malignant glioma U Naumann et al CD95L-induced apoptosis in these cells.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Despite the presumed role of XIAP in targeting caspases for proteasomal degradation, 9 the loss of XIAP did not result in an accumulation of procaspases, possibly because of autoactivation and autoprocessing. The loss of XIAP was delayed by the broad-spectrum caspase inhibitor, zVADfmk, suggesting that XIAP was not only depleted by antisense expression but also became a substrate for activated caspases, as previously observed during Ad-XIAP antisense gene therapy for malignant glioma U Naumann et al CD95L-induced apoptosis in these cells.…”
Section: Discussionmentioning
confidence: 89%
“…8 Further, IAP serve as ubiquitin ligases: they initiate ubiquitinylation of IAP-bound caspases and are therefore responsible for their proteasomal degradation. 9 The mitochondrial protein second mitochondrial activator of caspases (SMAC)/DIABLO promotes apoptosis by eliminating the protective effect of IAP through physical interactions, 10 which repress the ubiquitin ligase activity of XIAP and, to a lesser extent, of cIAP1 and cIAP2. 11 A second, alternative mechanism mediating XIAPdependent protection from apoptosis involves transcriptional activity mediated via the stimulation of NF-kB, which depends on the E3 ubiquitin ligase activity of the RING domain of XIAP.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, IAP induction may inhibit apoptosis in several cells [21,31,32]. Because of its ubiquitous distribution and inducible properties, the IAP family serves as cytoprotective machinery under bacterial toxin-stimulated pathophysiological situations [21].…”
Section: Discussionmentioning
confidence: 99%
“…IAP are ubiquitous, intracellular proteins that regulate apoptotic processes. Previous reports have shown that IAP are able to inhibit apoptosis induced by a wide range of stimuli, including TNF-a, anti-Fas antibodies, oxidative stress, pro-apoptotic members of the Bcl-2 family, cytochrome c, anticancer drugs, and serum withdrawal [29][30][31]. Because of its ubiquitous distribution and inducible property, the IAP family is supposed to serve as cytoprotective machinery under pathophysiological situations.…”
Section: Discussionmentioning
confidence: 99%